Exploring the impact of an interventional approach to resident teaching in anesthesiology clerkships - Carine Zeeni; Halah Ibrahim; Nathalie Khoueiry Zgheib; Elie Saliba; Marc Moukarzel; Reine Obeid; Nadine Abi Younes; Midhat Siddik; Gladys Honein Abou Haidar; Fatima Msheik-El Khoury (Medical Education Online)
Residents play a major role in medical student education during clinical clerkships. While various ‘Residents-as-Teachers’ (RAT) programs exist, few are tailored to anesthesiology, and little is known about students’ perceptions of effective teaching behaviors in this setting. This study aimed to evaluate the effectiveness of an educational workshop designed to improve the quality of resident teaching and to assess its impact on medical student learning outcomes and satisfaction. We also sought to identify specific resident teaching behaviors that students consider important for their learning and determine which of these behaviors improved post-intervention. The intervention targeted 1st to 3rd year clinical anesthesiology residents, and its effectiveness was evaluated through medical student feedback. We employed a pre-post-intervention design using a Quality of Supervision Questionnaire, with additional items on learning outcomes, career aspirations, and satisfaction. An open-ended question elicited students’ feedback on the behaviors of effective resident teachers. Data were analyzed using descriptive statistics and thematic analysis. Twenty-two residents participated in the intervention, and 132 medical students completed the questionnaires (77/106 pre, 55/58 post). Post-intervention, the mean score for the overall quality of teaching increased significantly (2.98 ± 0.53 pre vs. 3.40 ± 0.46 post, p < 0.001), with notable improvements across multiple domains. Student learning outcomes, interest in anesthesiology as a career, and rotation satisfaction improved significantly (p < 0.001). The percentage of students identifying effective teaching behaviors increased from 63% to 96%. Thematic analysis revealed more prevalent teacher characteristics and enhanced teaching strategies with a direct positive impact on learning. Our study emphasizes the importance of formal training for anesthesiology residents to enhance teaching quality and student learning. Findings provide effective resident teaching strategies which educators can use to refine training programs in anesthesiology. Future research should explore structured evaluations of resident perspectives on the training program and explore broader implementation across different specialties and institutions.